A survey on health prediction using human activity patterns through smart devices - Akhila, G.; Madhubhavana, N.; Ramareddy, N. V.; Hurshitha, M.; Ravinder, N. (International Journal of Engineering and Technology, 2017)
The world is devoting massively towards digital transformation to provide a healthier environment for people who live in smart homes. In such a change millions of smart devices are being equipped around, which gives a massive amount of refined and sorted data which is used to analyze the health patterns. In this research, the work mainly focuses on analyzing the human activity patterns for health prediction through smart devices. This survey includes frequent pattern mining, cluster analysis, the measure and analysis of the energy utilization changes accordingly by household. This paper represents the survey depends on the needs of analyzing energy utilization patterns of the appliance level, which completely depends on the human activity patterns.